Data for "A Confidence Map based Damage Assessment Approach using Pulsed Thermographic Inspection" - Zhao, Yifan (Cranfield University, 2017)
The data for the paper accepted by NDT E International.The zip contains txt files and also .raw and .mat which require Matlab.
Keywords: 'NDT'; 'Reliability'; 'Thermography'; 'Impact damage assessment'; 'Composite'; 'Manufacturing Engineering not elsewhere classified'